DINAMIKA KEPUSTAKAWANAN DAN ARSIP DI BALI - Sanjiwani, Ketut Ayu; Ginting, Richard Togaranta; Dewi, Desak Putu Sukma Kartika (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 3 No 1 (2023), 2023)
Libraries and librarians who need each other and cannot be separated, a library without a librarian will  work if there is no one to direct it and vice versa. Currently, librarianship activities are growing due to  advances in information technology. This development requires librarians to be able to master  information technology in practice which is becoming a global world trend. This change makes the  library need to prepare a development strategy to face challenges and maintain library performance  in meeting the information needs of increasingly diverse users. The development of the librarian  system is something that is done to perfect the existing system including activities to study, develop,  analyze, criticize the work of the library and examine the development of the librarian system. There  is a relationship between libraries and archives, namely archives as evidence of an activity in the form  of information media that is created and received by institutions or organizations and needs to be  managed according to the needs of each institution or organization. In addition, it is also needed for  simplification in managing and ease of carrying out the implementation process. In addition, a library  needs to have goals that must be achieved so that it can keep abreast of developments, especially in  the field of information technology and can continue to make technological improvements so that  managing activities in the library can run optimally.